Adoption of corporate governance best practices and existence of compliance committee affecting company performance: The case of top 100 Malaysia listed companies - Ong, Zhan Hao (2023)
This study aims to investigate the effects of corporate governance (CG) best practices on the performance of the top 100 PLCs in Malaysia. The design of this study is quantitative and longitudinal, using panel data analysis and descriptive analysis. Data is collected from companies’ annual reports and Refinitiv Terminal for the period of FY2013 to FY2021. The target population is companies listed on BURSA's Main Market, and the sample consists of the top 100 PLCs in Malaysia with the largest market capitalization as at 31 December 2022. A stratified sampling technique is employed, resulting in a sample size of 900 firm-observations representing nine financial years of 100 companies. The findings of the study reveal that the adoption of CG practices among the top 100 PLCs in Malaysia is decent, although there is still some room for improvement in certain areas, such as gender diversity and the establishment of a compliance committee. Additionally, study's panel data analysis yielded insightful results, revealing a significant negative relationship between ID-ROE, ID-TQ, OCTSR, and ECC-ROE, while demonstrating a significant positive relationship between WD-TQ. However, the IVs such as CEOD, IDAC, and BS were found to have insignificant impacts on company performance. Thorough discussion on the findings were provided in Chapters 4 and 5. The study's findings have managerial and theoretical implications that can be of value to policymakers, managers, investors, and other stakeholders interested in improving CG practices and enhancing company performance. The study highlights the need for regulatory bodies and companies to take an active role in promoting gender diversity, achieving a well-balanced composition of their board of directors, and considering the potential benefits of compliance committees. Theoretical implications suggest that the relationship between CG best practices and company performance may be more intricate than previously understood, and future research is needed to explore alternative factors that may influence this relationship.